Effect of Organic Composts in Red Amaranth and Spinach Productivity and Soil Fertility (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted at the experimental farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during December 2009 to March 2010 to study the effect of household wastes compost, palli compost and quick compost on growth and yield of red amaranth and spinach and improvement of soil fertility. The first time red amaranth and spinach were grown using compost and inorganic fertilizers, while the second time crops grown using only residual nutrients in soil. Yield data revealed that combined application of organic and inorganic fertilizers were significantly better than the solitary application of inorganic fertilizers. The fresh yield of red amaranth in the second harvest where no fertilizers were used recorded 13 t ha-1, which appeared significantly higher over the first harvest (10 t ha-1) and there was no significant difference between the yields of first and second harvest of spinach (18 t ha-1). Different composts increased OM, N, P and K contents, which indicated the fertility improvement of soil. The performance of composts at the rate of 20 t ha-1 in producing yields of vegetables was insignificantly different with the rates of 5-10 t ha-1. Among the different composts, household waste is available in the rural areas and its preparation is easy with minimum costs. Therefore, considering the availability and costing, household waste compost at the rate of 5-10 t ha-1 is recommended as a soil amendment for improving soil fertility and crop productivity. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22195 J. Environ. Sci. & Natural Resources, 7(2): 1-6 2014